Fear of Cyberattacks and Measure Efficacy among Students in Higher Education: The Sequential Roles of Perceived Severity and Perceived Vulnerability - Sofyan, Vina Annisa; Khaira Ummah; Mushaf (Information Technology Education Journal, 2026)
Purpose – This study examines the effect of fear of cyberattacks on measure efficacy among students in higher education and investigates the sequential roles of perceived severity and perceived vulnerability. Design/methods/approach – A quantitative approach was employed using an online survey of 203 university students selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings – The results show that fear of cyberattacks significantly influences perceived severity (β = 0.754, t = 13.487, p < 0.001), perceived severity significantly influences perceived vulnerability (β = 0.295, t = 4.374, p < 0.001), and perceived vulnerability significantly influences measure efficacy (β = 0.310, t = 4.613, p < 0.001). In addition, perceived vulnerability significantly mediates the relationship between perceived severity and measure efficacy (β = 0.091, t = 2.469, p = 0.014), while perceived severity and perceived vulnerability jointly mediate the relationship between fear of cyberattacks and measure efficacy (β = 0.069, t = 2.189, p = 0.029). Research implications/limitations – The study is limited by its cross-sectional design, self-reported responses, and focus on university students. However, the findings suggest that cybersecurity education in higher education should strengthen students’ understanding of threat severity and personal vulnerability to improve protective efficacy. Originality/value – This study contributes to information technology education by extending Protection Motivation Theory to explain how emotional and cognitive processes shape students’ protective efficacy in digital environments.